124 Outcomes of NT-probnp assay measurements in suspected heart failure in primary and secondary care settings. (6th June 2022) - Giannoudi, Marilena; Simpson, Bronwyn; Kandasamy, Vigneswaran; Wahab, Ali; Gosai, Jivendra; Jamil, Haqeel; Bulugahapitiya, Sudantha
Abstract : Background: Though N-terminal pro B type natriuretic peptide (NT-proBNP) testing in primary care is integral for evaluating patients with suspected heart failure and acts as a cost-effective gate-keeper to determine patients requiring echocardiography, its routine use in the hospital setting remains variable. Aim: 1. Comparison of NT-proBNP testing patterns in primary and secondary care settings. 2. To determine requirements for downstream echocardiography in patients with suspected heart failure in the two settings. Methods: 200 consecutive NT-proBNP lab results were reviewed. Data was collected outlining the location of the BNP test (inpatient vs outpatient), accompanying echo and CXR results, patient demographics and cardiac co-morbidities. NT-proBNP readings were graded into low (<400ng/l), intermediate (>400-<2000ng/l) and high risk(>2000ng/l) of left ventricular systolic dysfunction (LVSD) as per current guidelines. Statistical analysis was undertaken with IBM SPSS software. Results: A total of 180 patients comprised our analysis (exclusions included patients aged <18 and incomplete data). The mean age of patients was 67 (range 19–101). There was equal representation of both genders; 90 females and 90 males. The mean BNP value was 4407. 60 patients had values of <400ng/L, associated with a low probability diagnosis of heart failure, 51 with an intermediate risk and 79 with a high risk (value >2000ng/L). 110 tests (61%) were performed on inpatients. The NT-proBNP range was 30–79811ng/L, mean 5915ng/L. Of this cohort 24.5% had a low probability BNP value. The negative predictive value of inpatient BNP testing corresponding to preserved systolic function was 0.89. Of the remaining 75.5% of patients with a raised NT-proBNP (>400), 45% had evidence of LVSD on echocardiography. 70 NT-proBNP tests were performed on outpatients. The mean value was 2038 ng/L. Of this group 47% had a low probability BNP value. Of the 53% of patients with intermediate and high risk NT-proBNP values, 16 (43%) had imaging evidence of LVSD. Pearson's correlation coefficient was calculated at 0.970 with a significance of <0.001 for the relationship between inpatient and outpatient testing of low-risk NT-proBNP values. Conclusion: 1. In both primary and secondary care settings NT-proBNP testing can reduce the demand on cardiac echo services for evaluating suspected LVSD patients.2. NT-proBNP testing in primary care is more effective than in secondary care at identifying patients who do not require echo for LVSD evaluation.3. Pathways should be developed advocating greater use of naturetic peptides in the hospital setting to aid diagnosis and triage of patients who need to be assessed for suspected HF. Conflict of Interest: Nil